The Constitutional Challenges of the Judiciary in the Post-socialist Legal Systems of Central and Eastern Europe - Badó, Attila (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
Despite theoretical experimentation, although one cannot speak of a separate post-socialist legal family, it is without a doubt that CEE, post-socialist countries – and more precisely, the countries aspiring for EU membership – have had to cope with similar problems since the 1990s. Among the difficulties concerning the transition from dictatorship to democracy, a political – or rather, professional – discourse that mostly occurs in constitutional courts and is aimed at the true nature and the method of ensuring judicial independence has been and is now given more emphasis in Western countries as well. Independence from party politics or governmental authority plays an increasingly important role in CEE countries since the collusion of the single-party state and courts frequently had tragic consequences during the Stalinist period (the later and milder phase of the dictatorship in some countries was not always associated with an unfailing prevalence of judicial independence either, although direct political pressure could not be detected in a considerable part of legal disputes. In light of this saddening historical period, it is understandable that the chances of party political aspects that appear are more resounding than usual in post-socialist societies. Such fears are predominant in a narrow social stratum since the system of CEE political traditions, a weakened democratic legacy and frail or malfunctioning autonomies result in indifference towards institutional changes concerning the judicial independence as well. In this study, the most important constitutional foundations of the judicial systems of post-socialist CEE countries are presented. The judicial system of the assessed legal systems is presented by defining the constitutional bases and the rules laid down in the most important laws through the presentation of the literature on the institution. Having clarified the structural issues and the constitutional status of the courts – the central forms of administration – an assessment is conducted as to how well-known aspects of judicial independence and accountability play a role in the administration of justice of a given legal system. At the heart of the analysis is the much-misunderstood concept of judicial independence. Within this, the organisational independence of the judiciary, which determines the relationship of courts with other branches of power, on the one hand, determines the actual margin of appreciation of judges, and on the other hand, it may shed light on the reforms of CEE judicial systems on their way to democracy following dictatorship and the single-party system. The above may also reveal how these systems tried to meet the requirements of European accession  and how they responded to societal needs. Although the system of the organisation of the judiciary in post-socialist countries has also undergone changes, mainly due to constitutional amendments aimed to enforce the principle of access to justice, no analysis of the changes is conducted here due to a lack of space. Although we can talk about a broader and narrower meaning of the concept of justice, in this chapter, the situation of CEE legal systems based on the narrower concept is also presented for reasons of length. Thus, we specifically deal with courts, which are the central actors in the application of the law. We also dispense with the presentation of constitutional courts’ activities, to which this volume devotes a separate chapter. At the beginning of this chapter, we conduct an analysis of how the Court of Justice of the European Union and the Council of Europe, which connects the wider Europe, interpret the concept at its heart: judicial independence. Afterwards, we discuss the constitutional fundations and the central administration of courts. As a conclusion, we outline possible ways of development in post-socialist judicial systems.KEYWORDS: Judiciary, Constitutional challanges, Post-socialist legal systems, Judicial Councils, Administration of justice.